IMPLEMENTASI KEBIJAKAN TATA RUANG BERBASIS LINGKUNGAN UNTUK MENCEGAH BANJIR DI KAWASAN PERKOTAAN - Sutiana, Asep (Jurnal De Lege Ferenda Trisakti, 2025)
Rapid growth in urban areas often results in uncontrolled land use changes, ignoring the presence of green open spaces as regulated in Law Number 26 of 2007 on Spatial Planning, and worsening the risk of flooding. Implementation of environmentally-based spatial planning policies is important to reduce these negative impacts. The problems faced are low compliance with spatial planning policies and lack of coordination between stakeholders in implementing policies that consider environmental aspects. The purpose of this study is to analyze the effectiveness of implementing environmentally-based spatial planning to prevent flooding in urban areas. This study uses a normative legal approach, which focuses on the analysis of laws and regulations, spatial planning policies, and laws governing the environment and their application in an urban context. The results of the study indicate that the development of green open spaces, improving natural drainage systems, and utilizing environmentally friendly technologies contribute to reducing the risk of flooding in urban areas. However, there are still challenges in implementation that require synergy between the government, community, and private sector.